NLPPort: A Pipeline for Portuguese NLP - Rodrigues, Ricardo; Oliveira, Hugo Gonçalo; Gomes, Paulo (My University, 2018)
Although there are tools for some the most common natural language processing tasks in Portuguese, there is a lack of available cross-platform tools specifically targeted for Portuguese, from end to end, namely for integration in projects developed in Java. To address this issue, we have developed and tweaked, over the last half-dozen years, NLPPort, a set of tools that can be used in a pipelined fashion, which we have made publicly available. In this paper, we present the major features of such set of tools.
Keywords: natural language processing; tools; Portuguese